2011
DOI: 10.2478/s13380-011-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

Towards a neuroimaging biomarker of depression vulnerability

Abstract: Major depressive disorder (MDD) is a pervasive and debilitating illness, with a recurrent course and chronic prognosis. Although effective treatments for MDD exist, there is a pressing need to characterize relapse vulnerability in order to design effective prophylactic care. To date, heterogeneity within depression neuroimaging research has made it difficult to establish a reliable biomarker of disorder susceptibility. In this paper, we review neuroimaging evidence for the assessment of MDD vulnerability, theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 172 publications
0
3
0
Order By: Relevance
“…Consistent with these hypotheses, MBCT may reduce excessive connectivity within the default mode network (Farb et al, 2007, 2011; Taylor et al, 2013), possibly reflecting strengthened present-moment awareness (e.g., Fresco et al, 2007b). Similarly, Fresco et al (2017) examined the associations between pretreatment neural patterns of intrinsic functional connectivity in hubs within the DMN to treatment-related changes in worry and decentering in generalized anxiety disorder patients (with and without MDD) receiving emotion regulation therapy (e.g., Fresco, Mennin, Heimberg, & Ritter, 2013; Mennin, Fresco, Ritter, & Heimberg, 2015).…”
mentioning
confidence: 67%
“…Consistent with these hypotheses, MBCT may reduce excessive connectivity within the default mode network (Farb et al, 2007, 2011; Taylor et al, 2013), possibly reflecting strengthened present-moment awareness (e.g., Fresco et al, 2007b). Similarly, Fresco et al (2017) examined the associations between pretreatment neural patterns of intrinsic functional connectivity in hubs within the DMN to treatment-related changes in worry and decentering in generalized anxiety disorder patients (with and without MDD) receiving emotion regulation therapy (e.g., Fresco, Mennin, Heimberg, & Ritter, 2013; Mennin, Fresco, Ritter, & Heimberg, 2015).…”
mentioning
confidence: 67%
“…A series of studies have validated decentering as a construct important in the acute and enduring treatment of MDD and anxious depression (Fresco, Moore, et al, 2007; Fresco, Segal, et al, 2007; Mennin & Fresco, 2011) and in the prevention of MDD relapse following prophylactic treatment with MBCT (Bieling et al, 2012). fMRI assessment and neural correlates of treatment following MBCT revealed that normalization of mPFC activity coupled with an ability to approach emotion provocation with a nonjudgmental, nonreactive, awareness-predicted treatment durability (Farb, Segal, & Anderson, 2011).…”
Section: Treating Refractory Self-referential Processingmentioning
confidence: 99%
“…32 Neuroimaging research has recently shown that hypoactive prefrontal activation coupled with hyperactive limbic system activation represents altered DMN function that could serve as a brain-based biomarker for vulnerability to mental disorders, including depression and substance abuse. 33-36 Some of the latest clinical and mechanistic research on the DMN has demonstrated that DMN activity is modifiable through meditation practice. Specifically, yoga meditation has been associated with greater functional connectivity between the DMN and other distributed brain networks involved in attention, self-referential processing, and affective responses, and mindfulness meditation has been shown to increase somatosensory processing, decrease cognitive elaboration associated with the narrative self, and diminish emotional reactivity in the limbic system.…”
Section: Introductionmentioning
confidence: 99%